Analisis Strategi Langkah Mundur dan Bernalar Logis dalam Menentukan Bilangan dan Nilainya - Landyasari Riffyanti; Rubono Setiawan (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2017)
This study analyzed the mathematical problem solving strategy that combines a backward step and reasoned logically to answer the High School Olympic level problems related to number theory for the district, national, and provincial level which are often issued from year to year. The mentioned problem is more about the application of number theory problem, which is determine a number and the value of the questioned number. The study began by analyzing some Olympic problems. These problems are answered and resolved by a combination of mathematical problem solving strategies, which are backward step and reasoned logically. Implementation of this solving problem should also be adjusted with Polya step which is consists of four stages. Polya step is used to give better structured problem solving. Compared with trial and error method, this analyze can give an effective combination to determine a number and the value of a number.